PENGARUH MEDIA TUTUP BOTOL ANGKA TERHADAP KEMAMPUAN MENGURUTKAN BILANGAN ANAK USIA 4-5 TAHUN DI TK ISLAM AL-FURQON PEDAMARAN - Imelia, Imelia; Ilhami, Akmillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of number bottle cap media on the number sequencing ability of children aged 4–5 years at TK Islam Al-Furqon Pedamaran. The research employed a quantitative experimental approach using a one-group pretest–posttest design involving 16 children selected through total sampling. Data were collected through observation sheets and documentation, and were analyzed using normality and hypothesis testing. The average score of children’s number sequencing ability increased from 48.3 in the pretest to 84.5 in the posttest, showing an improvement of 36.2 points. The Shapiro–Wilk normality test indicated that both pretest and posttest data were normally distributed (pretest Sig. = 0.281; posttest Sig. = 0.334). Based on the paired sample t-test using SPSS version 26, the significance value (Sig. 2-tailed) was p < 0.001, which is smaller than the significance level of 0.05, with a t-value of −19.915. These findings indicate that number bottle cap media is effective and has a significant effect on the number sequencing ability of children aged 4–5 years because it provides concrete, visual, and interactive learning experiences; therefore, this media can be used to support cognitive development, particularly in early childhood number sequencing skills, and can also stimulate children’s language, physical-motor, and social-emotional development.